2020
DOI: 10.2217/epi-2020-0162
|View full text |Cite
|
Sign up to set email alerts
|

Potential Use of Noncoding RNAs and Innovative Therapeutic Strategies to Target the 5’UTR of SARS-CoV-2

Abstract: After the increasing number of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections all over the world, researchers and clinicians are struggling to find a vaccine or innovative therapeutic strategies to treat this viral infection. The severe acute respiratory syndrome coronavirus infection that occurred in 2002, Middle East respiratory syndrome (MERS) and other more common infectious diseases such as hepatitis C virus, led to the discovery of many RNA-based drugs. Among them, siRNAs and ant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 83 publications
1
51
0
1
Order By: Relevance
“…Epigenomic studies might open new avenues for developing antiviral drugs by evaluating specific epigenetic modulators as targets and exploring new chromatin-based therapies for different virus families, including Coronaviruses, which could reveal fundamental new landscapes of virus–host interaction and their role in disease severity [ 85 ]. Previous works focused on specific epigenetic mechanisms [ 83 , 101 ]. This article summarizes the comprehensive knowledge about epigenetic aspects associated with SARS-CoV-2 infection and suggests potential epigenetically based therapies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Epigenomic studies might open new avenues for developing antiviral drugs by evaluating specific epigenetic modulators as targets and exploring new chromatin-based therapies for different virus families, including Coronaviruses, which could reveal fundamental new landscapes of virus–host interaction and their role in disease severity [ 85 ]. Previous works focused on specific epigenetic mechanisms [ 83 , 101 ]. This article summarizes the comprehensive knowledge about epigenetic aspects associated with SARS-CoV-2 infection and suggests potential epigenetically based therapies.…”
Section: Resultsmentioning
confidence: 99%
“…RNA-based drugs are other epigenetic tools that should be investigated for treating viral infections [99,100]. For instance, among all the SARS-CoV genome that have been under study so far, Baldassarre and coworkers suggested that the 5′URT region and specific portion of it, which are essential for viral RNA replication and transcription, could be considered relevant to design novel therapeutic molecules to treat the infection [101]. Novel strategies employing small interfering RNAs (siRNAs), microRNAs (miRNAs), and locked nucleic acid antisense oligonucleotides (LNA) or GapmeRs, targeting, for instance, the 5′URT or regions of the Spike molecule, represent potential therapeutic tools for both prophylaxis and therapy of COVID-19 [101][102][103].…”
Section: H5n1-vn1203mentioning
confidence: 99%
See 1 more Smart Citation
“…While some progress has been made by repurposing the RNA polymerase inhibitor Remdesivir (5) or by ameliorating SARS-CoV-2 induced lung injury using Dexamethason (6), lethality of COVID-19 remains high (7). A promising alternative approach could be to deliver small interfering (si)RNAs (8)(9)(10)(11) to the respiratory tract by inhalation (12) and induce degradation of viral RNAs by the RNA-interference (RNAi) machinery. Studies performed with Severe Acute Respiratory Syndrome Coronavirus-1 (SARS-CoV-1) or Middle East Respiratory Syndrome Coronavirus (MERS-CoV), showed that siRNAs can silence viral RNA and relieve symptoms caused by related coronaviruses (13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Studies performed with Severe Acute Respiratory Syndrome Coronavirus-1 (SARS-CoV-1) or Middle East Respiratory Syndrome Coronavirus (MERS-CoV), showed that siRNAs can silence viral RNA and relieve symptoms caused by related coronaviruses (13)(14)(15)(16)(17). However, while several publications have proposed siRNAs as potential therapeutic also for COVID-19 (8)(9)(10)(11), until today there is no proof that SARS-CoV-2 can be inhibited by siRNAs, not to mention a detailed systematic analysis, which replication steps are accessible for RNAi. SARS-CoV-2, as other coronaviruses, has a positive sense, single-stranded RNA genome with a length of approximately 30,000 nucleotides.…”
Section: Introductionmentioning
confidence: 99%